Pengaruh Praktek Bibliometrik Etika Bisnis Dan Csr Menciptakan Nilai Jangka Panjang Perusahaan - Ryan Maulana; Masiyah Kholmi (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This research aims to explore the influence of using bibliometric methods in identifying literature on business ethics and Corporate Social Responsibility (CSR) on the creation of long-term value for companies. Bibliometric methods are used to analyze and present research trends, theoretical contributions, and best practices related to this topic. Through a literature synthesis, this research identifies the relationship between ethical business practices and CSR with increasing public trust, strengthening relationships with stakeholders, and a positive impact on the company's long-term performance. The results of this research are expected to provide valuable insights for academics, practitioners and managers in strengthening ethical and CSR practices as strategies for achieving sustainability and sustainable company growth.